Implikasi Hukum Atas Kelalaian Notaris Terhadap Keterlambatan Pendaftaran Jaminan Fidusia - Subekti, Hadi; Fatmwati Octarina, Nynda (UNES Law Review, 2024)
The legal implication of notary negligence for late registration of fiduciary guarantees is that notary acts are very risky and have a negative impact, so it is necessary to provide fair and appropriate legal protection to the parties involved in the transaction. This study aims to remind and encourage notaries to comply with applicable legal provisions carefully and in a timely manner. In addition, it is also to uphold justice and legal certainty in fiduciary guarantee transactions, so that the rights and obligations of each party can be fulfilled properly. By applying appropriate legal implications for notary negligence, it is expected to prevent violations of law that harm the parties and maintain the integrity of the notary profession as a trustworthy law enforcer. The research method used is normative legal research. With a statutory approach, i.e. examining current laws and regulations, other relevant literature, and case studies relating to the topic of legal implications of notary negligence on late registration of fiduciary guarantees. The results showed that the legal implications of notary negligence in the process of registering fiduciary guarantees can be very detrimental to the parties involved in the transaction. Moreover, the lack of regulatory clarity and the lack of a conducive legal culture can be obstacles in carrying out notary duties effectively. However, the notary's role in ensuring the validity and legal force of the fiduciary guarantee deed is essential to provide protection to the parties concerned.